PENERAPAN MODEL PROBLEM BASED LEARNING PADA PEMBELAJARAN PERSAMAAN GARIS LURUS DI KELAS VIII SMP NEGERI 2 TAHUNA - Alfraldo Lahaube; James U.L Mangobi; Derel F. Kaunang (LPPM Universitas Bina Bangsa, 2023)
This study aims to determine the average difference in the learning outcomes of straight-line equations material for students who are taught using the Problem Based-Learning model and the average learning outcomes for straight-line equations material for students who are taught using the Direct Instruction model. The design of this research is the Posttest Only Control Design. This research was conducted at SMP Negeri 2 Tahuna in the even semester of the 2022/2023 academic year. The subjects in this study were taken into 2 classes, namely class VIII B as the experimental class and class VIII C as the control class. Data collection was carried out by giving tests in the form of questions to both classes after being given treatment. The research data were analyzed using t-test statistics and the calculation results showed that the t_count=5.48 > t_table=1.68. Because the value of t_count > t_table then reject H0. Thus it can be concluded that the average student learning outcomes straight line equation material experimental class is more than the average student learning outcomes control class